Effect of DEDEN-PjBL Model on Children's Creativity - Sadaruddin, Sadaruddin; Syamsuardi, Syamsuardi; Usman, Usman; Hasmawaty, Hasmawaty; Nasaruddin, Nasaruddin (Lembaga Sembilan Tiga Community, 2024)
This study aims to measure the effect of applying the Design, Explain, Develop, and Evaluation-Project Based Learning (DEDEn-PjBL) model on creativity in children. The research method is a quasi-experimental quantitative method with a non-equivalent one-group design by comparing pre-test and post-test values. Sampling used a saturated sample with a total of 15 students. Data was collected with an observation sheet in the form of a checklist. The collected data were analyzed using descriptive and inferential statistics using the paired sample t-test. The results of the data analysis showed that the mean posttest was higher than the mean pretest. The hypothesis test shows that the calculated t value is greater than the t table value with a significance value of 0.00, so it can be concluded that applying the DEDEn-PjBL model can increase children's creative abilities.